Water balance and the irrigation need of rice in different agro ecological regions of Sri Lanka - Weerasinghe, K. D. N., author; Sabatier, J. L., author; Attanayake, W. S., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Daily rainfall and pan evaporation in 22 locations of Sri Lanka for more than 35 consecutive years were analyzed to assess the Agro climatic potential of different regions in respect to moisture availability, for which the computer program "first" was developed. In the program Markov chain procedure is employed to analyze dry and wet spells; forward and backward rainfall accumulation probability curves are incorporated to decide upon the crop establishment time and the point at which two curves are bisected was considered as the probability at which the particular crop could be grown. Water balance of the localities were assessed using the Hargreave's Moisture availability Index (MAI) and Troll's criteria. The program CROPWAT was used to estimate irrigation need to plot the rainfall, evaporation, water balance, crop performance probability and irrigation need maps. From the stand point of the water balance approach for Yala and Maha seasons two hydrologic regions, namely humid and semi-arid regions are identified for the Maha season (fig.3) and three hydrological regions viz. Humid, Semi-arid, and Arid regions, in Yala season. The entire dry zone remains arid in the Yala season (fig.4) Crop commencement in these regions could be done in 42nd - 43rd weeks. Performance probability of rice in the "Maha" season appeared to be lowest in Hambantota and Puttalam, and highest at Batticaloa, Trincomalee and Polonnaruwa areas. It was established that irrigation need in Maha and Yala seasons as 597-1000 mm, (except Hambantota area) and 1200-1300 mm.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.